3D printed devices and infrastructure for liquid sample delivery at the European XFEL. (15th February 2022) - Vakili, Mohammad; Bielecki, Johan; Knoška, Juraj; Otte, Florian; Han, Huijong; Kloos, Marco; Schubert, Robin; Delmas, Elisa; Mills, Grant; de Wijn, Raphael; Letrun, Romain; Dold, Simon; et al.
Abstract : Presented here are 3D printed sample delivery devices for precise control over fluids and the generation of micrometre‐sized gas‐focused liquid jets, high‐viscosity streams and near‐monodisperse droplets suitable for X‐ray scattering experiments on X‐ray free‐electron laser (XFEL) instruments. Abstract : The Sample Environment and Characterization (SEC) group of the European X‐ray Free‐Electron Laser (EuXFEL) develops sample delivery systems for the various scientific instruments, including systems for the injection of liquid samples that enable serial femtosecond X‐ray crystallography (SFX) and single‐particle imaging (SPI) experiments, among others. For rapid prototyping of various device types and materials, sub‐micrometre precision 3D printers are used to address the specific experimental conditions of SFX and SPI by providing a large number of devices with reliable performance. This work presents the current pool of 3D printed liquid sample delivery devices, based on the two‐photon polymerization (2PP) technique. These devices encompass gas dynamic virtual nozzles (GDVNs), mixing‐GDVNs, high‐viscosity extruders (HVEs) and electrospray conical capillary tips (CCTs) with highly reproducible geometric features that are suitable for time‐resolved SFX and SPI experiments at XFEL facilities. Liquid sample injection setups and infrastructure on the Single Particles, Clusters, and Biomolecules and Serial Femtosecond Crystallography (SPB/SFX) instrument are described, this being the instrument which is designated for biological structure determination at the EuXFEL.